(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The excellence of the tourism sector is allegedly a source of new economic drivers, which is included in the category of comparative special advantages if it has the existence of resources to be managed in the long term. Tourism does not constantly improve the economy, this is based on the conditional state of tourism which is not a basic sector of the economy. The Tourism-Led-Growth Hypothesis states that tourism contains non-linear variables because the state of tourism output affects various thresholds of the economy not constantly. This study analyzes 20 countries with the highest TTCI index in 1991-2021. Time series data, using the threshold effect statistical method by building a model of tourism on the economy. The research will also prove the relevance of the Tourism-Led-Growth Hypothesis, which states tourism must be comparative and have a threshold value to affect the economy. The results confirm that Threshold Effects of the Tourism-Led Growth is very relevant and accurate in knowing how influential the variable components of tourism affect the economy through non-linear relationships. Non-linear relationships must be formed because it characterized tourism variables as not always constant, but sometimes tourism affects the economy minimally and optimally. From the results of the 20 countries with the highest TTCI Index values, the countries that have significant tourism variables and affect the economy both at the minimum and optimum limits are 13 countries. The tourism sector in these 13 countries is specialized and has a comparative advantage, so it can affect the economy at the minimum and optimal threshold values. In the results of 7 countries proven that tourism is not specialized and does not affect the economy either at the minimum or optimal threshold, 7 countries do not have a comparative advantage and are not specialized in tourism.